2012
DOI: 10.1210/en.2012-1698
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Estradiol Administration in Aging Ovariectomized Rats Provides Lasting Benefits for Memory and the Hippocampus: A Role for Insulin-Like Growth Factor-I

Abstract: We previously demonstrated that aged ovariectomized rats that had received prior estradiol treatment in middle age exhibited enhanced spatial memory and increased levels of estrogen receptor (ER)-α in the hippocampus long after estradiol treatment was terminated. The implication for cognition of increased levels of ERα resulting from prior estradiol exposure is unknown. In the absence of estrogens, growth factors, including IGF-I, can induce ERα-mediated transcription through ligand-independent mechanisms. Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 57 publications
10
59
2
1
Order By: Relevance
“…The current findings indicating that IGF-1 can activate ER␣ and increase levels of ER␣-regulated proteins in the hippocampus provide a potential mechanism by which ER␣ can be activated and impact cognition in the absence of circulating estrogens. The functional implications for cognition of activation of IGF-1 receptors in the absence of circulating estrogens are evident from previous data from our lab in which antagonism of brain IGF-1 receptors blocked the lasting enhancing effects on cognition in aging ovariectomized rats that had previous estradiol exposure (18). In addition, this chronic antagonism of hippocampal IGF-1 receptors reversed the lasting elevation in hippocampal levels of ER␣ and ChAT that was evident in aging females that had previous estradiol treatment.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The current findings indicating that IGF-1 can activate ER␣ and increase levels of ER␣-regulated proteins in the hippocampus provide a potential mechanism by which ER␣ can be activated and impact cognition in the absence of circulating estrogens. The functional implications for cognition of activation of IGF-1 receptors in the absence of circulating estrogens are evident from previous data from our lab in which antagonism of brain IGF-1 receptors blocked the lasting enhancing effects on cognition in aging ovariectomized rats that had previous estradiol exposure (18). In addition, this chronic antagonism of hippocampal IGF-1 receptors reversed the lasting elevation in hippocampal levels of ER␣ and ChAT that was evident in aging females that had previous estradiol treatment.…”
Section: Discussionsupporting
confidence: 52%
“…An incision was made in the scalp and fascia that overlie the skull. A hole was drilled in the skull and a 10l Hamilton syringe was lowered to the appropriate depth [coordinates: -0.3 mm anterior-posterior, ϩ1.2 mm medial-lateral, and -4.5 mm dorsal-ventral relative to bregma (18)]. IGF-1 (GroPep, Adelaide, Australia), 2 g/l (25) in a total volume of 1ul or aCSF vehicle (Tocris Bioscience, Bristol, UK) was delivered over a period of 2 minutes.…”
Section: Infusion and Tissue Dissectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like oestradiol, IGF1 is a neuroprotective hormone and a local factor that contributes to maintain body and tissue homeostasis, including the regulation of brain plasticity and function 108 . The neuroprotective actions of oestradiol and IGF1 have many points in common, and both factors interact in the regulation of neuronal survival, neuritogenesis, adult neurogenesis, brain cholesterol homeostasis, glucose metabolism, neuroprotection and cognition 82,[109][110][111][112][113][114][115] .…”
Section: Brain-derived Neurotrophic Factormentioning
confidence: 99%
“…Therefore, it is conceivable that secondary effects of GH deficiency are more important for the cognitive deficits than impaired brain GHR signaling per se. Several studies have shown that IGF-1 signaling has neuroprotective and neurodevelopmental effects and also influences cognitive processes (Miltiadous et al 2011;O'Kusky and Ye 2012;Aberg et al 2006;Witty et al 2013;Le Greves et al 2005;Molina et al 2013;Sonntag et al 2013;Ramis et al 2013). However, the wide distribution of GH-responsive cells in areas involved in mechanisms of learning and memory, as well as in emotional/motivational processes, provides neuroanatomical evidence that GH signaling may directly affect cognitive processes and the expression of behaviors, independently of changes in IGF-1 circulating levels.…”
Section: Possible Functional Implications Of Gh-responsive Cells In Tmentioning
confidence: 99%